1992
DOI: 10.1111/j.1749-6632.1992.tb21063.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr Viral Latency and Cell Immortalization as Targets for Antisense Oligomersa

Abstract: The approach of using an antisense oligonucleotide to oppose the synthesis of a single selected viral gene product needed to maintain the EBV episome in non-virus-producing cells appears to be promising not only for possible cure of latent viral infection, but also for reversal of EBV-driven cell proliferation. It is also possible that targeting multiple latent viral genes might mount a synergistic effect that would prove to be more efficient at curing latent infection. However, further work is needed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…For these reasons, we sought to determine whether antiviral approaches targeting the EBNA-1 protein could inhibit EBV-induced cell proliferation. Previous studies showed that antisense oligonucleotides directed to EBNA-1 partially inhibited EBNA-1 expression and also suppressed B cell proliferation (28,29). However, sufficient quantities of antisense oligonucleotides cannot be efficiently delivered to B cells and their relatively short half-life inside cells has hindered utilization of this antiviral approach.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we sought to determine whether antiviral approaches targeting the EBNA-1 protein could inhibit EBV-induced cell proliferation. Previous studies showed that antisense oligonucleotides directed to EBNA-1 partially inhibited EBNA-1 expression and also suppressed B cell proliferation (28,29). However, sufficient quantities of antisense oligonucleotides cannot be efficiently delivered to B cells and their relatively short half-life inside cells has hindered utilization of this antiviral approach.…”
Section: Discussionmentioning
confidence: 99%
“…1B, lanes 5 and 6; Fig. 3D, lanes 1 and 2; also data not shown) (34,51). In contrast, the IRF-1 level is basically unchanged in type I and III cells.…”
Section: Expression Of Irf-2 Is Associated With Ebv Type III Latencymentioning
confidence: 91%
“…Latency types were confirmed by detection of EBNA1, EBNA2, and LMP1 proteins by Western blot analysis with specific antibodies (data not shown). IRF-7A was also expressed at a higher level in SFC-4 and CB95 cells, which are type III (33), than in Akata type I cells (reference 45 and data not shown). Therefore, without exception, in all the cell lines tested, the expression of IRF-7 is greater in type III than in type I latency.…”
Section: Cloning Of Irf-mentioning
confidence: 99%